Developing Simple Android Applications On Websites With MIT App Inventor For Students of SMAN 4 Bogor City - Hilman Jihadi; Aryanti Kristantini; Harjo Baskoro; Dade Maulana; Sofwan Muhammad (International Journal Of Community Service, 2024)
SMAN 4 Bogor is high school under the supervision of the Ministry of Education and Culture in the South Bogor sub-district, Bogor city. Located 3 km from zero point Bogor city. This paper presents a workshop on Developing Simple Android Applications Based on Websites with MIT App Inventor conducted for students of SMAN 4 Kota Bogor by lecturers from the Faculty of Computer Science, Information Systems Department, Institut Bisnis Informatika Kosgoro. The workshop aimed to equip students with the skills to create Android applications, understand coding workflows, and conduct application testing. The hands-on training allowed students to apply their knowledge in developing simple everyday applications. The results indicate that students enjoyed the Android, computer, and website-based learning approach, finding it easier to grasp the subject matter. Additionally, there was a noticeable increase in their knowledge of information technology. This was evidenced by their increased engagement and comprehensive understanding during technology-based learning sessions. Students were able to develop simple applications for daily use, demonstrating the workshop's effectiveness in enhancing their technological proficiency.